Halal Industry Development in Brunei Darussalam: Realities and Challenges - Sulaiman, Nor Surilawana; Abdullah, Rose; Hashim, Norkhairiah (KnE Social Sciences, 2023)
The global halal market is witnessing significant growth, estimated at USD 2.41 trillion, and this upward trend is expected to continue due to increasing worldwide demand. In response to this lucrative opportunity, Brunei is actively supporting Micro, Small, and Medium Enterprises (MSMEs) and providing necessary facilities to foster the development of the halal industry in the country. This article aims to explore the current realities of Brunei’s halal sector by examining the factors that contribute to the rising demand for halal products and the opportunities presented by recent market developments. The research employed a method of assessing secondary data from various sources to achieve its objectives. The results highlight several factors influencing the development of the halal industry in Brunei. It is evident that the future growth of this sector hinges on industry players’ ability to expand their understanding of product sales and effective promotion strategies. The findings from this study can serve as a valuable resource for future researchers, academics, and policymakers when making informed decisions about the halal industry in Brunei. Keywords: Brunei, challenges, development, halal industry, realities